ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN BERKUNJUNG KE HOTEL DI KOTA JEMBER PADA SAAT PANDEMI COVID-19 - Hadi Jatmiko; Syah Riza Octavy Sandy (Universitas Muhammadiyah Jember, 2020)
This study will discuss an analysis of the analysis of factors affecting the decision to visit hotels in Jember City during the Covid-19 pandemic. So that through this research it can contribute ideas to hotel service business actors in making policies to increase the level of guest visits in the current Covid-19 pandemic situation. This study aims to (1) analyze the factors that influence guests 'decisions to stay at hotels during the Covid-19 pandemic, (2) analyze the dominant factors that influence guests' decisions to stay at hotels during the Covid-19 pandemic. The population of this study were guests who decided to visit the hotel with proportional random sampling of 100 respondents, structured interviews with hotel management associations. The results showed that (1) Simultaneously: Health protocol factors, staff capability, accessibility, and room facilities were proven to influence jointly on guest visiting decisions during the Covid19 pandemic in Jember, (2) Staff ability has a dominant influence on Guest Visit Decisions during the Covid19 Pandemic in the city of Jember. This shows that hotel staff must understand services during the Covid-19 pandemic, especially regarding health protocols